The Evolution of Research on Globalization and Consumer Behavior: A Bibliometric Analysis (2006-2024) - Saud, Hari Singh; Kumar, Rajender; Chataut, Ram Kumar (Journal of Durgalaxmi, 2025)
The interaction between globalization and consumer behavior has been a central focus of both academic and industry research for decades. This study delineates the conceptual structure, trends, topics, and major themes in globalization and consumer behavior research from 2006 to 2024 using bibliometric analysis. The data analyzed using Biblioshiny software under the R programming. The study analyzed 3,143 documents obtained from the Web of Science and Scopus databases, focusing on productivity by authors, institutions, and countries, co-citation, keyword co-occurrence, and thematic clustering. The findings indicate that the most pertinent source was “Environmental Science Pollution Research,” and Adebayo T was identified as the most prominent author, having contributions of 57 publications. The most significant institution was the Cyprus International University, that accounted for 66 publications. China emerged as the leading contributor by producing 1,904 publications. The thematic clusters showed increasing interest in sustainability, policy-oriented research, renewable energy, and digital consumer identities. This study synthesizes 18 years of literatures and offers a roadmap for future research on globalization, technology, and consumer culture.